Parents’ Opinions about their Children’s Distance Learning during the First Wave of the Covid-19 Pandemic - Maja Drvodelić; Vlatka Domović (Center for Educational Policy Studies Journal, 2022)
Due to the Covid-19 pandemic, distance education became the only official form of instruction in all schools in Croatia for a period commencing 16 March 2020. This situation changed the expectations, roles and responsibilities of parents with regard to the teaching and learning process of their children. Understanding parents’ experiences during school closure is important for the development of recommendations for similar situations. This paper presents part of the results of an online survey investigating the opinions of 1,205 parents of primary school children on various aspects of distance education. The responses were analysed by researchers using the thematic analysis approach. The initial answers of parents regarding the positive and negative aspects of education during the lockdown were grouped into categories. The results indicate that distance education positively contributed to the development of children’s self-regulated learning and to providing greater parental support in learning, as well as empowering children in using ICT. Parents emphasise positive changes in the quality of family relationships, which are partly the consequence of joint learning with their children and partly due to changes in the way of life during the lockdown. Negative aspects can be divided into two general categories, the first of which is linked to children (e.g., lack of support from school, lack of children’s interest in learning), while the second refers to the challenges faced by parents (e.g., fear of school failure, undertaking the double role of custodian and teacher). The findings suggest the need for the development of recommendations that would provide support for parents and children in situations where the teaching and learning process take place in an online environment.